3D multilayered Bi4O5Br2 nanoshells displaying excellent visible light photocatalytic degradation behaviour for resorcinol. (1st August 2018) - Hu, Hanmei; Xu, Juanjuan; Deng, Chonghai; Wang, Man; Zhou, Xiaoyu; Le, Huirong
Abstract : High‐ordered three‐dimensional multilayered Bi4 O5 Br2 nanoshells have been fabricated successfully via a green ultrasound‐assisted anion exchange reaction followed by a calcination treatment approach. The products are characterised by X‐ray diffraction, field‐emission scanning electron microscopy, transmission electron microscopy, high‐resolution transmission electron microscopy, UV–vis diffuse reflectance spectrum and N2 adsorption/desorption isotherms. The results reveal that ternary Bi4 O5 Br2 nanoshells possess a pure monoclinic phase with the average thickness of ca. 12 nm, and the walls are of 10–12 layers constructed by nanograins with 10 nm in size. The specific surface is measured to be 36.18 m 2 g ‐1 and the band gap energy E g value is calculated to be 2.52 eV. The possible formation process for Bi4 O5 Br2 nanoshells is simply proposed. According to the photocatalytic degradation for resorcinol under visible light irradiation, the as‐prepared Bi4 O5 Br2 nanoshells exhibit excellent photocatalytic performance, which is not only far beyond the degradation rate of BiOBr precursor nanosheets but also superior to that of other reported Bi4 O5 Br2 architectures, suggesting a practical application for the treatment of organic pollutants.